Quality changes of different varieties of pepper during natural fermentation process - ZHENG Rong, HE Xufeng, XIONG Shuang, HU Lu, YI Liangjian, HUANG Wenping, LONG Chao, HUANG Xiaolan (Zhongguo niangzao)
Chopped pepper was prepared with Xiaomila and Erjingtiao as raw materials, the changes of physiochemical indexes and sensory quality of chopped pepper during natural fermentation process was analyzed, and the effects of fermentation time and pepper variety on the quality of chopped pepper were investigated. The results showed that the pH, total sugar content of the 2 kinds of chopped peppers showed a decreasing trend, the contents of total acid, organic acid, free amino acid, and capsaicin compounds contents increased first and then tended to be stable, and the amino acid nitrogen increased first and then decreased. The sensory score of chopped pepper was the highest after fermentation for 50 d, forming the optimum flavor with rich flavor, moderate sour taste and slightly weak spicy taste, indicating that fermentation for 50 d was suitable as the end point of fermentation. The quality of chopped pepper fermented with Erjingtiao was better than that of Xiaomila after fermentation for 50 d, the pH, total acid, total sugar, amino acid nitrogen, organic acid, free amino acid, capsaicin compounds contents and sensory score were 4.79, 0.73 g/100 g, 8.23 g/100 g, 0.25 g/100 g, 27.76 mg/kg, 3 724.11 mg/kg, 361.00 mg/kg, and 91, respectively.